Gender identity and sexual orientation in Austrian adolescents. - Lukas Teufl; Friedrich Teutsch; Roman Winkler (PLOS Global Public Health)
In many European countries, representative data on the proportion of lesbian, gay, bisexual, transgender, and queer (LGBTQ) adolescents are still lacking. Therefore, this study used data of 9,295 adolescents (11 to 17 years) who participated in two nationwide surveys (Health Behaviour in School-aged Children Study and Austrian Health Study on Apprentices) and investigated answers regarding gender identity and sexual orientation. Additionally, age- and gender-specific patterns and mocking answers given were quantitatively and qualitatively analyzed. Results show that 0.8% of Austrian adolescents identified with a gender other than female or male and 10.5% with a sexual orientation other than heterosexual, with other sexual orientations being more common in girls (14%) than boys (4%). Only five adolescents were unsure about their gender identity and every twentieth adolescent did not identify with a sexual orientation yet. Most adolescents took the questionnaire seriously, with only 82 (0.8%) mocking answers given. These mocking answers were classified in seven groups, with Popular Culture and Memes being the largest group. This study makes a significant contribution to the collection of data on gender identity and sexual orientation of (Austrian) adolescents.